2018
DOI: 10.1101/284752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paracingulate sulcus morphology and hallucinations in clinical and non-clinical groups

Abstract: Hallucinations are a characteristic symptom of psychotic mental health conditions that are also experienced by many individuals without a clinical diagnosis. Research has linked the experience of hallucinations in schizophrenia to differences in the length of the paracingulate sulcus (PCS), a structure in the medial prefrontal cortex of the brain which has previously been associated with the ability to differentiate perceived and imagined information. We Measurements of paracingulate sulcal length were compare… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 63 publications
2
13
0
Order By: Relevance
“…A functional systems approach can also help us to understand how atypicalities in one part of a system can be compensated for by flexibility in its other components (Luria, 1965; Fernyhough, 2010). For example, it is possible that AH in patient groups can be distinguished from AH in individuals who do not seek clinical help (so-called ‘non-clinical’ hallucinators) in terms of two interacting processes: a modality-general reality-monitoring system in the prefrontal cortex and a modality-specific increase in resting activation in auditory areas (Garrison et al ., 2019). Elevated baseline activation in auditory cortex areas has previously been implicated in AH (Hunter et al ., 2006), and in the terms of the present article would count as a modality-specific process.…”
Section: Network-specific Processes: a Functional Systems Approachmentioning
confidence: 99%
“…A functional systems approach can also help us to understand how atypicalities in one part of a system can be compensated for by flexibility in its other components (Luria, 1965; Fernyhough, 2010). For example, it is possible that AH in patient groups can be distinguished from AH in individuals who do not seek clinical help (so-called ‘non-clinical’ hallucinators) in terms of two interacting processes: a modality-general reality-monitoring system in the prefrontal cortex and a modality-specific increase in resting activation in auditory areas (Garrison et al ., 2019). Elevated baseline activation in auditory cortex areas has previously been implicated in AH (Hunter et al ., 2006), and in the terms of the present article would count as a modality-specific process.…”
Section: Network-specific Processes: a Functional Systems Approachmentioning
confidence: 99%
“…Limitations: In Study 1, we restricted our participants to healthy controls and patients with schizophrenia with hallucinations and due to difficulties identifying suitable participants for recruitment, we did not include a third group of patients with no life-time experience of hallucinations. As such, we cannot be sure that our finding linking paracingulate functional connectivity with reality monitoring impairment also extends to the association between paracingulate morphology and hallucinations in schizophrenia (10,11). While much previous work has identified a reality monitoring impairment associated with hallucinations in schizophrenia (13), this point provides a focus for replication and extension of the current study.…”
Section: Discussionmentioning
confidence: 54%
“…Reality monitoring ability, as measured by recollection of the perceived vs. imagined aspects of context, is associated with functional activity and connectivity within the medial prefrontal cortex (mPFC) (4)(5)(6), consistent with the role of cortical midline structures more generally in self-referential processing (7)(8)(9). This is further supported by evidence linking the structural morphology of the paracingulate sulcus (PCS) region of the mPFC to both reality-monitoring ability in healthy individuals (2), and to the experience of hallucinations in patients with schizophrenia (10,11). While there is currently no causal evidence linking reality monitoring ability to functionality either generally within the mPFC, or more specifically within paracingulate cortex, it is suggested that altered activity and functional connectivity within this brain region may underlie the behavioural reality monitoring impairments observed in schizophrenia patients, contributing to their experience of hallucinations (12)(13)(14).…”
Section: Introductionmentioning
confidence: 55%
“…Here we studied two ethnically independent structural MRI datasets of patients with schizophrenia (n = 181) and healthy controls (n = 63) to empirically test theoretical predictions linking hallucinations, cortical folding patterns, and salience and auditory brain network congruity. We first directly replicated, in this larger sample, the reduced left PCS length in schizophrenia patients with hallucinations compared to those without (8,25), showing ethnic invariance (26) of a prenatally-determined structural marker for hallucinations. To render this tractable for large datasets, a semi-automated method was used to detect and characterize the PCS and STS from T1-weighted MRI, which we validated against the prior, gold standard manual approach.…”
Section: Introductionmentioning
confidence: 77%